ANALISIS DETERMINAN PROFITABILITAS BANK SYARIAH DI ASEAN (INDONESIA, MALAYSIA, BRUNEI DARUSSALAM) - Mohammad Yudhi Ramadhani; M.Faisal Abdullah; Sri Budi Cantika (Jurnal Ilmu Ekonomi JIE, 2019)
This research aims to analyze the determinant of the profitability of Sharia banks in ASEAN that took 3 countries, namely Indonesia, Malaysia, and Brunei Darussalam. This study uses 24 sharia banks in 3 ASEAN countries. The sampling used in this research is the purposive sampling method, which is the uptake based on the criteria that have been established. This method of research is quantitative. The data collection method used is with the documentation. The data required is secondary data from the financial reporting data of each sharia bank in Indonesia, Malaysia, and Brunei Darussalam in 2013-2017. The data analysis technique is a data panel regression analysis technique. The results of the study showed that on average the ROE percentage of Sharia banks in Indonesia reached 0.81%. For simultaneous testing also due to the value of F-count 34.75609 ≥ F-table 3.13 Then it can be concluded that H0 rejected and H1 accepted, which means that the free variables i.e. CAR, FDR, NPF, and BOPO are influential simultaneously and together against variable bound is ROE Bank Syariah in Indonesia, Malaysia, and Brunei Darussalam in 2013-2017.